The impact of introducing new stops into the agglomeration railway network on changes in transport behaviour in the catchment area - Sabina Puławska-Obiedowska; Aleksandra Ciastoń-Ciulkin; Mariusz Soboń (Archives of Transport)
The aim of the analysis is to examine the impact of new railway stop openings within suburban railway network on changes in transport behaviors within their respective catchment areas. The study focuses on six railway stations: four located within the Kraków suburban railway network (malopolskie, Poland) and two on the Łódź suburban railway network (lodzkie, Poland). To achieve the stated objective, the spatial context and accessibility of the railway stations were examined, passenger exchange data at the stations were investigated, and surveys among passengers were conducted and analyzed. The selected railway stops were characterized in terms of their spatial location and characteristics, existing transport systems, and the level of integration with other transport modes. The study examined stations established during the development of suburban railway systems, launched at different times: concurrently with the entire railway connection launch and as densification of previously served networks. The limited number of objects included in the study does not allow for unequivocal conclusions on expected increase in transportation, but certainly, in the first two years following their launch, a monthly average increase of 4-6% can be anticipated. Research has confirmed that the most common rail passengers are former users of other means of public transport. The pattern of giving up cars in favor of the train was also confirmed. The outcomes confirm the justification for supplementing agglomeration railway systems with new stops, as this may contribute to a change in modal split. This change may not be noticeable in view of the usually considered large scale of the agglomeration, but on individual corridors in a micro scale it may have a very positive impact on the traffic situation and change the quality of travel. Results can be used to forecast changes in travel behaviors for planned railway stations and to determine their potential benefits.